Advantages of Dose-Dense Methotrexate Protocol for Primary Central Nervous System Lymphoma: Comparison of Two Different Protocols at a Single Institution - Aoki, Hiroshi (Neurol Med Chir (Tokyo), 2013)
The efficacy and toxicity of high-dose methotrexate (HD-MTX)-based chemotherapy were retrospectively reviewed in patients with primary central nervous system lymphoma (PCNSL). All immunocompetent patients with histologically or radiographically diagnosed PCNSL treated between 2006 and 2012 at Niigata University Hospital were enrolled. Thirty-eight patients with a diagnosis of PCNSL were treated with one of two regimens during different time periods. During the first period, from 2006 to 2009, three 3-week cycles of MPV (MTX + procarbazine + vincristine) were administered (MPV3 group). In the second period, from 2010 to 2012, five 2-week cycles of MTX were administered (MTX5 group). High-dose cytarabine was used in both groups following HD-MTX-based chemotherapy. Whole-brain radiotherapy was used for patients who did not attain a complete response (CR) based on magnetic resonance images. In the MPV3 group, 20 out of 23 patients (87%) completed the planned treatment. The CR rate after chemotherapy was 30%, and 57% after radiation therapy. Thirteen out of 15 patients (87%) in the MTX5 group completed the planned treatment. The CR rates after chemotherapy and radiation therapy were 53% and 93%, respectively. Renal dysfunction was assessed by measuring creatinine clearance rates, which were very similar in both groups. In terms of hematologic toxicity and other adverse reactions, there was no significant difference between the two groups. In conclusion, dose-dense MTX chemotherapy improved outcome with acceptable toxicity compared with the treatment schedule for three cycles of MPV treatment.